Internet Of Things(IoT) Digital Forensic Investigation Model: Top-Down Forensic Approach Methodology - Perumal, S; Norwawi, NM; Raman, V (IEEE, 2024)
The Internet of Things (IoT) is the interconnection of uniquely identifiable embedded computing devices within the existing Internet infrastructure. Typically, internet of things (IoT) is expected to offer advanced connectivity of devices, systems, and services that goes beyond machine-to-machine communications (M2M) and covers a variety of protocols, domains, and applications. The interconnection of these embedded devices including smart objects, is expected to usher in automation in nearly all fields, while also enabling advanced applications like a Smart Grid. The main research challenge in Internet of things (IoT) for the forensic investigators is based size of the objects of forensic interest, relevancy, blurry network boundaries and edgeless networks, especially on method for conducting the investigation. The aim of this paper is to identify the best approach by designing a novel model to conduct the investigation situations for digital forensic professionals and experts. There was existing research works which introduce models for identifying the objects of forensics interest in investigations, but there were no rigorous testing for accepting the approach. Currently in this work, an integrated model is designed based on triage model and 1-2-3 zone model for volatile based data preservation.